The organizational structure for environmental protection in Malaysia. - Baba, Hanim Norza; Jusoff, Kamaruzaman (David Publishing Company, USA, 2009)
Management has addressed the critical issue of environmental protection by developing environmental management systems. The purpose of this research is to describe the organizational structure for environmental protection, an attribute of environmental management systems of privately held companies, certified with MS ISO 14001. Descriptive statistics are reported for the primary data. The commonly reported attributes provide evidence of high-level commitment to environmental protection: written environmental policy statement, corporate-level environmental management function, and Board of Directors' responsibility for oversight of environmental affairs. Findings indicate that companies have educational programs and environmental goals to disseminate environmental management values throughout their organizations.